Jews and India : Mutual Influences over Two Millennia - Katz, Nathan, (Brill | Manohar Publishers & Distributors, 2023)
The entire set of sixteen essays in Jews and India explore a particular interaction and mutual influence between Jews and India over the past two millennia. Collectively, we discover a pattern of uniquely symmetrical relations between Jews and their host culture. Unlike in the Christian and Islamic countries, Jews were always honored and treated in India like respected guests. We all come to know ourselves through our reflections in the eyes of others, and rather than hostility and a condescending attitude, in India, Jews always enjoyed respect, hospitality, and affection. These chapters seek to answer the theoretical question as to what Jews and Judaism looked like when viewed with a 'good eye'. Conversely, we also learn how the world sees Jews who have always enjoyed respect and were made welcome. The first section of the book analyzes Jewish communities in Kochi, especially, but also the Bene Israelis and Baghdadis. Following is a section of stories about individual Jewish lives in India - mystics, merchants, and soldiers. The book concludes with a section about inter-religious dialogues between Jews and Indic faiths like Hindus, Buddhists and Jains. Based on two thousand years of cohabitation, these old/new friendships reveal old surprises and new insights.